Pengaruh Terapi Pendamping Aktivitas Fisik Home-Based Walking Exercise Selama 45 Menit Terhadap Kadar Glukosa Darah Acak pada Pasien Diabetes Melitus Tipe 2 - Novia Rofiqoh Arifah; Ach. Arfan Adinata; Moch. Bahrudin; Sri Utami (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2024)
Introduction:  Type 2 diabetes mellitus is often called the mother of all diseases which can result in complications. The risk of complications increases over the age of 40 years, so physical activity is needed to improve blood flow and increase the effectiveness of insulin use in the body. Objectives: This study aimed to determine the effect of home-based walking exercise companion physical activity therapy for 45 minutes on random blood glucose levels in patients with type 2 diabetes mellitus. Methods:  This research design uses a quasi-experimental one-group pretest-posttest. The sampling technique uses a non-probability sampling technique: purposive sampling. The sample for this study was 19 patients with type 2 diabetes mellitus at the Puskesmas Lidah Kulon. Data were collected using an observation sheet on the results of random blood glucose clinic examinations. Statistical test data analysis used the Wilcoxon signed rank test with α < 0,05.  Results: The results of the study showed that the average random blood glucose level before implementation was 247,9474 and after implementation, it was 196,8947. The statistical test results obtained p value 0,00<0,05, which means H1 is accepted.  Discussion: The results of the study show that home-based walking exercise companion physical activity therapy for 45 minutes affects reducing random blood glucose levels in patients with type 2 diabetes mellitus